2017
DOI: 10.1377/hlthaff.2017.0945
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Wisely Campaign: Valuable For Providers Who Knew About It, But Awareness Remained Constant, 2014–17

Abstract: Together with physician specialty societies, the Choosing Wisely® campaign has codified recommendations of which health care services' use should be questioned and discussed with patients. The ABIM Foundation administered surveys in 2014 and 2017 to examine physicians' attitudes toward and awareness of the use of low-value care. The surveys included questions on the factors driving that use, physicians' comfort in having conversations with patients about that use, and physicians' exposure to the Choosing Wisel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 32 publications
1
33
2
Order By: Relevance
“…This can be very challenging, however, due to the complexity of insurance coverage. Utilize choosing wisely and other society recommendations to avoid low‐value care …”
Section: Strategies To Reduce Financial Toxicitymentioning
confidence: 99%
“…This can be very challenging, however, due to the complexity of insurance coverage. Utilize choosing wisely and other society recommendations to avoid low‐value care …”
Section: Strategies To Reduce Financial Toxicitymentioning
confidence: 99%
“…and "just to be safe" (78%). [34] Egerton-Warburton et al [35] found that over half of 1029 emergency physicians in the study reduced their implicit "test threshold" well below the explicit threshold set using empirical data on test accuracy and risk of harm from the disease, due to their discomfort with diagnostic uncertainty. [35] Coon et al [16] also highlighted the "shotgun approach" [16] of ordering a broad range of tests and hoping for a positive result somewhere, which is often used in situations of diagnostic uncertainty.…”
Section: Fear Of Malpractice and Litigationmentioning
confidence: 95%
“…This factor was cited in 22 articles. In the 2017 American Board of Internal Medicine Foundation survey, [34] among the commonest reasons for ordering low value tests were desire to reduce uncertainty (84%)…”
Section: Fear Of Malpractice and Litigationmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Choosing Wisely has garnered impressive support from both clinician societies and consumer advocacy groups, such as Consumer Reports, in developing a collaborative approach to tackle overuse. Nevertheless, widespread awareness and implementation have been difficult to achieve, 4,5 and patient engagement and understanding of overuse remain challenging.…”
Section: Etter To the Editormentioning
confidence: 99%